Ecology and spatiotemporal dynamics of sandflies in the Mediterranean Languedoc region (Roquedur area, Gard, France). Issue 1 (December 2015) - Prudhomme, Jorian; Rahola, Nil; Toty, Céline; Cassan, Cécile; Roiz, David; Vergnes, Baptiste; Thierry, Magali; Rioux, Jean-Antoine; Alten, Bulent; Sereno, Denis; Bañuls, Anne-Laure
Abstract Background Phlebotomine sandflies are hematophagous insects widely present in Western Mediterranean countries and known for their role asLeishmania vectors. During the last ten years, the risk of leishmaniasis re-emergence has increased in France. However, sandfly biology and ecology in the South of France remain poorly known because the last detailed study on their spatiotemporal dynamics was performed over 30 years ago. The aim of the present study was to update our knowledge on sandfly ecology by determining their spatiotemporal dynamics and by investigating the relationship between environmental/climatic factors and the presence and abundance of sandflies in the South of France. Methods An entomological survey was carried out during three years (2011–2013) along a 14 kilometer-long transect. The findings were compared with the data collected along the same transect in 1977. Data loggers were placed in each station and programmed to record temperature and relative humidity every six hours between April 2011 and November 2014. Several environmental factors (such as altitude, slope and wall orientation (North, East, West and South)) were characterized at each station. Results Four sandfly species were collected:Phlebotomus ariasi andSergentomyia minuta, which were predominant, Ph. perniciosus andPh. mascittii . Sandfly activity within the studied area started in May and ended in October with peaks in July-August at the optimum average temperature. We found a positive effect of altitude and temperature and a negative effect of relative humidity onPh. ariasi andSe. minuta presence. We detected interspecific differences and non-linear effects of these climatic variables on sandfly abundance. Although the environment has considerably changed in 30 years, no significant difference in sandfly dynamics and species diversity was found by comparing the 1977 and 2011–2013 data. Conclusion Our study shows that this area maintains a rich sandfly fauna with highPh. ariasi population density during the active season. This represents a risk forLeishmania transmission. The analysis revealed that the presence and abundance ofPh. ariasi andSe. minuta were differently correlated with the environmental and climatic factors. Comparison with the data collected in 1977 highlighted the sandfly population stability, suggesting that they can adapt, in the short and long term, to changing ecosystems.